2014
DOI: 10.2465/jmps.131022d
|View full text |Cite
|
Sign up to set email alerts
|

Secondary phosphates in montebrasite and amblygonite from Nagatare, Fukuoka Prefecture, Japan

Abstract: Montebrasite and amblygonite in an Li-Cs-Ta enriched (LCT) pegmatite from Nagatare, Fukuoka Prefecture, Japan, contain various alteration minerals: fluorapatite, crandallite, goyazite, waylandite, wardite, viitaniemiite, morinite, muscovite, lepidolite, and cookeite. They are associated with lacroixite, quartz, and topaz. Among these minerals, wardite, viitaniemiite, morinite, and lacroixite are newly discovered in Japan. The secondary phosphates and fine-grained mica form fine veins along cleavages and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…[ 76,78 ] Primary amblygonite–montebrasite is known to be prone to replacement by a large range of products, from simple hydration to form F‐poor montebrasite to Li leaching and addition of external elements ( e.g ., Na, Ca, and Fe) to make up complex phosphate minerals. [ 4,25,63,78 ] However, in this study, no other phases were observed at the studied scale. Consequently, the replacement of primary F‐rich montebrasite by secondary F‐poor montebrasite represents a progressive hydration process with concomitant F leaching by the fluid phase, represented by the F–OH exchange reaction: LiAl(PO 4 )(OH,F) ➔ LiAl(PO 4 )OH, or simply F − ➔ OH − .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…[ 76,78 ] Primary amblygonite–montebrasite is known to be prone to replacement by a large range of products, from simple hydration to form F‐poor montebrasite to Li leaching and addition of external elements ( e.g ., Na, Ca, and Fe) to make up complex phosphate minerals. [ 4,25,63,78 ] However, in this study, no other phases were observed at the studied scale. Consequently, the replacement of primary F‐rich montebrasite by secondary F‐poor montebrasite represents a progressive hydration process with concomitant F leaching by the fluid phase, represented by the F–OH exchange reaction: LiAl(PO 4 )(OH,F) ➔ LiAl(PO 4 )OH, or simply F − ➔ OH − .…”
Section: Discussioncontrasting
confidence: 54%
“…The mineral list is a part of the phosphates described in the Buranga pegmatite. [ 36,39 ] The placement of minerals in the diagram is based on natural observations of mineral relations, [ 4,25,38,39,63 ] experimental determinations of mineral stability, [ 20–22,64 ] and modified according to the author's observations [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Background Informationmentioning
confidence: 99%
“…1b) crossing first and second generations of amblygonite-montebrasite in all localities but only fresh in Montebras, Helikon I and McDonalds. The presence of two or more generations of amblygonite-montebrasite is frequently described in many similar deposits (Pirard, 2022;Shirose & Uehara, 2014;Galliski et al, 2012;Scholz et al, 2008;London & Burt, 1982). Cathodoluminescence spectra of amblygonite-montebrasite is not systematic although differences between the three generations can be observed (Fig.…”
Section: Lithium Phosphatesmentioning
confidence: 96%
“…4). Although Al 3+ in montebrasite is known to allow substitution with trivalent and tetravalent cations (Dias et al, 2011), most anomalies and variability between trace elements concentrations seem to be linked to the presence of micro-inclusions, as it is known in such phosphates (Shirose & Uehara, 2014). Veinlets of tertiary montebrasite, which are more transparent, have smoother trace elements patterns and display a clear enrichment in medium rare earth elements (REE) over light and heavy REE as well as an enrichment in alkalis and transitions metals.…”
Section: Li-bearing Phosphatesmentioning
confidence: 99%
“…EPMA shows a Mn-Mg-bearing viitaniemiite with the following composition: Na 0.93 (Ca 0.82 Mn 0.09 Mg 0.07 )Al 1.03 (PO 4 ) 0.99 (F 2.30 OH 0.72 ) (Table 4). Changes in cathodoluminescent colours can be correlated with Ca  Mn,Mg exchange and 2Na +  (Ca,Mn,Mg) 2+ (Shirose & Uehara, 2014;Petrík et al, 2011;Lathi, 1981). The first substitution leads to a viitaniemiite where manganese is more abundant than calcium (Fig.…”
Section: Viitaniemiite -Na(camn)al(po 4 )(Foh)mentioning
confidence: 99%